2017
DOI: 10.1007/s40135-017-0141-4
|View full text |Cite
|
Sign up to set email alerts
|

Extraocular Muscle Repair and Regeneration

Abstract: Purpose of Review The goal of this review is to summarize the unique regenerative milieu within mature mammalian extraocular muscles (EOMs). This will aid in understanding disease propensity for and sparing of EOMs in skeletal muscle diseases as well as the recalcitrance of the EOM to injury. Recent Findings The EOMs continually remodel throughout life and contain an extremely enriched number of myogenic precursor cells that differ in number and functional characteristics from those in limb skeletal muscle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 81 publications
4
47
0
Order By: Relevance
“…One potential explanation for the increased cross-sectional area of the GDNF-treated muscles is that GDNF might foster a proliferative response in the muscle regenerative populations. Pax7 is a transcription factor expressed on quiescent satellite cells in all skeletal muscles and plays an important role in skeletal muscle growth, repair, and regeneration [ 25 , 26 ], with elevated levels in extraocular muscles [ 27 ]. Analysis showed that there were no significant differences in the number of Pax7-positive satellite cells per myofiber number between any of the areas or regions ( Fig 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…One potential explanation for the increased cross-sectional area of the GDNF-treated muscles is that GDNF might foster a proliferative response in the muscle regenerative populations. Pax7 is a transcription factor expressed on quiescent satellite cells in all skeletal muscles and plays an important role in skeletal muscle growth, repair, and regeneration [ 25 , 26 ], with elevated levels in extraocular muscles [ 27 ]. Analysis showed that there were no significant differences in the number of Pax7-positive satellite cells per myofiber number between any of the areas or regions ( Fig 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we aimed to investigate if there were intrinsic trophic differences between muscle progenitors derived from the EOMs, the muscles of the tongue, the buccinator and the EDL, that could explain why the EOMs SCs show higher proliferative and fusion rates (reviewed by [44]), features that seem to be responsible for the extraordinary EOMs regenerative properties and their resistance to certain diseases [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the relative inaccessibility of EOMs we have used biopsies of orbicularis oculi muscle (OOM) as a surrogate orbital muscle to pro le transcripts which may closely resemble the EOM transcriptome. As craniofacial muscles both EOMs and OOMs share similar embryological origins and many of the anatomical, physiological and molecular characteristics which distinguish EOMs from skeletal limb muscle [12]. Both EOMs and OOMs have fast ring rates [13], high mitochondrial content and oxidative capacities [14,15] and type II bre predominance [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…As craniofacial muscles both EOMs and OOMs share similar embryological origins and many of the anatomical, physiological and molecular characteristics which distinguish EOMs from skeletal limb muscle [12]. Both EOMs and OOMs have fast ring rates [13], high mitochondrial content and oxidative capacities [14,15] and type II bre predominance [9,12]. Therefore, the use of OOMs as a surrogate for EOM will provide important validation of gene expression tissue-speci city of the craniofacial myotome in OP-MG vs normal controls.…”
Section: Introductionmentioning
confidence: 99%